2019
DOI: 10.3390/rs11040381
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Forest Vertical Structure from PolInSAR Data by Machine Learning Using LIDAR-Derived Features

Abstract: This paper presents a machine learning based method to predict the forest structure parameters from L-band polarimetric and interferometric synthetic aperture radar (PolInSAR) data acquired by the airborne UAVSAR system over the Réserve Faunique des Laurentides in Québec, Canada. The main objective of this paper is to show that relevant parameters of the PolInSAR coherence region can be used to invert forest structure indicators computed from the airborne LIDAR sensor Laser Vegetation and Ice Sensor (LVIS). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Linear regression between the lidar-based and PolInSAR-model-based vegetation height for the temperate and tropical forest showed a 0.89 coefficient of determination with 2.3 m RMSE and a 0.98 coefficient of determination with 2.1 m RMSE [81]. Several other studies were also conducted in which highly accurate results were reported by the researchers [68,[82][83][84][85].…”
Section: Discussionmentioning
confidence: 82%
“…Linear regression between the lidar-based and PolInSAR-model-based vegetation height for the temperate and tropical forest showed a 0.89 coefficient of determination with 2.3 m RMSE and a 0.98 coefficient of determination with 2.1 m RMSE [81]. Several other studies were also conducted in which highly accurate results were reported by the researchers [68,[82][83][84][85].…”
Section: Discussionmentioning
confidence: 82%
“…A SAR operating at wavelengths ranging from a few centimeters to a few meters is more sensitive to larger canopy components [2]. The main scatterers in a canopy are the elements having dimensions of the order of the wavelength as shown in Figure 2.…”
Section: Frequency Bands For Monitoring Forest Regions Using Polsar Smentioning
confidence: 99%
“…Besides the economic and commercial importance of the forests that provide timber and wood, forest canopy layer has a great role in providing vital ecosystem services [1,2]. Accordingly, the most common application in vegetation observation has become the estimation of the forest vertical structure with emphasis on accurate estimation of the canopy layer thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, classification of the composition of tree species and nationwide AGB estimations using only ALS data has proven to be a difficult task. Therefore, airborne and/or spaceborne optical and/or radar data are often used for tree species classification [12,13] and to upscale local or regional estimations to the national level [14,15].…”
Section: Introductionmentioning
confidence: 99%